Security Pricing and Deviations From the Absolute Priority Rule in Bankruptcy Proceedings. - Eberhart, Allan C; Moore, William T; Roenfeldt, Rodney L (Journal of Finance, 1990)
Claims ultimately awarded to shareholders of firms in reorganization were examined for a sample of thirty filings under the 1978 Bankruptcy Reform Act. The authors measured the amount paid to shareholders in excess of that which they would have received under the absolute priority rule and found that this amount represents, on average, 7.6 percent of the total awarded to all claimants. Evidence is also reported that common share values reflect a significant proportion of value ultimately received in violation of absolute priority, suggesting that deviations from the rule were expected by the equity markets.